ANALISIS NILAI BUDAYA SASTRA LISAN BATAK TOBA “BATU SIGADAP” - Enjelina Sinaga (JURNAL SASTRA INDONESIA (SASINDO), 2012)
Oral literature is the literary expression of literature that includes citizens, a culture that spread and handed down orally (word of mouth). Because of its spread from mouth to mouth, oral literature will be easy to fade. For that the solution offered is to raise the research on oral stories to maintain the existence of the oral literature. Legend of Batu Sigadap is one form of oral literature Batak Toba community property, which is precisely Silalahi Silahisabungan District, Dairi. This study aimed to describe the composition of the stories and events that happened in the legend  Batu Sigadap, structured and translated into a story and explore the cultural values ​​contained therein. This research is a qualitative descriptive study, prioritize the meaning and context, the role of researcher of high demand. Informants in this study there were seven people in the two cultural experts Silalahi, one Raja Adat in Silalahi, three people Silalahi, and one journalist in Silalahi. The latter finding of this study is that there are eight cultural values, cultural values ​​of the nine major Batak Toba in  Batu Sigadap story, the cultural values ​​of kinship, religion, conflict, law, hasangapon, hamoraon, hagabeon and protection. Based on this research, the value of cultural kinship says there are five events, religion and conflict each said there are three events, while the value of legal culture, hasangapon, hamoraon, hagabeon each said there are two events and cultural values ​​aegis of the event said. Batu Sigadap oral literature, which is considered as a judge in the Silalahi believed to have supernatural powers to know the truth, based on research, until now Batu Sigadap still feared and trusted, which is why Batu Sigadap Silalahi sacred by the community.   Key word: Cultural values, Batak Toba, Oral Literature, Batu Sigadap.